Association of Lipid Accumulation Product With Insulin Resistance and Metabolic Syndrome in Type 2 Diabetic Patients In Relation With Dietary Habit in Bangladeshi Population (Bangladesh Journal of Medicine, 2022)
Background: Lipid accumulation product (LAP) is a novel biomarker of central lipid accumulation related to diabetes and cardiovascular disease risk. In this study, we assessed the association of LAP with glucose homeostasis, lipid profile parameters, and some clinical parameters about fast food-taking habits of diabetic patients. This study evaluated the relationship between lipid accumulating product (LAP) with insulin resistance and metabolic syndromeinfast food-taking patterns in the Bangladeshi type 2 diabetic population.Methods: Three hundred and seventy-five T2DM subjects as cases and three hundred and seventy-five healthyindividuals as control were assessed for anthropometric and biochemical measurements. LAP was calculated as [waist circumference (cm)–65]×[triglycerides (mmol/L)] in men, and [waist circumference (cm)–58]×[triglycerides (mmol/L)] in women. Associations of LAP with fasting glucose, insulin, insulin resistance index, and lipid profile levels, were assessed. Fast food-taking habits per week were also taken from the study subjects. Some clinical parameters (BMI, blood pressure, and waist-hip ratio) were also measured.Results: LAP was significantly correlated with glycemic markers like FBG, ABF,F. Insulin,HBA1C, HOMA-IR, HOMA B%, and Serc-HOMA in type-2 DM subjects. The p-value was less than 0.001. This study was alsosignificantly (p=